The work of having a chronic condition: development and psychometric evaluation of the distribution of co-care activities (DoCCA) scale - Ulrica von Thiele Schwarz; Marta Roczniewska; Karin Pukk Härenstam; Klas Karlgren; Henna Hasson; Sivan Menczel; Carolina Wannheden (BMC, 2021)
Abstract Background Chronic care involves multiple activities that can be performed by individuals and healthcare staff as well as by other actors and artifacts, such as eHealth services. Thus, chronic care management can be viewed as a system where the individual interacts with people and eHealth services performing activities to maintain or improve health and functioning, called co-care. Yet, the system perspective is not reflected in concepts such as person-centered care and shared decision making. This limits the understanding of individuals' global experience of chronic care management and subsequently the ability to optimize chronic care. The aim of this study was threefold: (1) to propose a theory-based operationalization of co-care for chronic care management, (2) to develop a scale to measure co-care as a distributed system of activities, and (3) to evaluate the scale's psychometric properties. With the theory of distributed cognition as a theoretical underpinning, co-care was operationalized along three dimensions: experience of activities, needs support, and goal orientation. Methods Informed by the literature on patient experiences and work psychology, a scale denoted Distribution of Co-Care Activities (DoCCA) was developed with the three conceptualized dimensions, the activities dimension consisting of three sub-factors: demands, unnecessary tasks, and role clarity. It was tested with 113 primary care patients with chronic conditions in Sweden at two time points. Results A confirmatory factor analysis showed support for a second-order model with the three conceptualized dimensions, with activities further divided into the three sub-factors. Cronbach's alpha values indicated a good to excellent reliability of the subscales, and correlations across time points with panel data indicated satisfactory test-retest reliability. Convergent, concurrent and predictive validity of the scale were, overall, satisfactory. Conclusions The psychometric evaluation supports a model consisting of activities (demands, unnecessary tasks, and role clarity), needs support and goal orientation that can be reliably measured with the DoCCA scale. The scale provides a way to assess chronic care management as a system, considering the perspective of the individuals with the chronic condition and how they perceive the work that must be done, across situations, either by themselves or through healthcare, eHealth, or other means.